Mindfulness in a Digital World - Harley, Dave. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
Using a lens of mindfulness, this book explores how digital dependencies can displace attention and undermine attentional control, leading to experiences of stress and mindless involvement with digital technology. Using qualitative interviews with teachers and students of mindfulness programmes, the book explores the challenges and opportunities for reconciling digital interactions with mindful practice. A phenomenological analysis of participants' digital experiences shows three different imperatives (relating to digital capabilities, hyper-reality and algorithms), that can drive unconscious forms of interaction and encourage a delegation of attentional control that draws users away from the present moment. The book concludes by exploring the implications of these (extra-conscious) imperatives for understanding digital addiction. It also provides a set of guidelines for a digital approach to mindfulness practice that can encourage beneficial relationships with digital technology into the future. Dave Harley is Principal Lecturer at the University of Brighton and a Committee Member of the BPS Cyberpsychology Section. His research explores older people's appropriation of digital technologies and issues relating to the extended digital self. He co-authored the 2018 book: Cyberpsychology as Everyday Digital Experience across the Lifespan.
Chapter 1. Digital Wellbeing: Making Sense of Digital Dependency -- Chapter 2. What is Mindfulness? -- Chapter 3. Mindfulness in the Context of Digital Habits -- Chapter 4. Digital Approaches to Mindfulness.
Keywords: Social psychology; Psychology; Mass Media; Positive psychology; Digital media; Buddhist philosophy; Social Psychology; Media Psychology; Positive Psychology; Digital and New Media; Buddhist philosophy